META ANALYSIS: MANAGEMENT CONTROL SYSTEM, STRATEGY, COMPANY PERFORMANCE - Pujiati, Desi; ., Margianti; ., Misdiyono (APTIKOM Publisher, 2019)
This study aimed at determining and analyzing the meta analysis on journals review of the managementcontrol system, strategy and company performance theme. The management control system used lever's approach ofcontrol consisting of belief system, boundary system, diagnostic control system and interactive control system. Theinfluence and impact of the management control system was resulted from previous research studies. This researchused meta-analysis method. Meta-analysis is the study of a number of research results in similar problems. The unit ofanalysis in the study were written documents about the research of management control system in the form of journalarticles and research reports taken purposively based on their compatibility with the research theme. Data analysisused was quantitative data analysis with percentage and qualitative data analysis for descriptive analysis result dataon 25 research related to management control system. Findings of meta-analysis results based on research objectives,research variables used, population / sample of research, data collection techniques and analysis tools show thatmanagement control system lever's of control approach can contribute to the achievement of strategy and impact onbusiness unit performance improvement.